PERTUMBUHAN EKONOMI PERSPEKTIF EKONOMI ISLAM - Moch. Zainuddin (Istithmar: Jurnal Studi Ekonomi Syariah, 2017)
The economy growth country is characterized by an increase in the greater income of a country. This means that the economy is not stagnant. That’s because the number of goods & services produced more and more. The logical implication of the increase of state revenues and the ease of public access to obtain goods and services needed is the welfare and quality of life of the community is increasing as well. However, the people should face the facts that what happened just the opposite. On economic growth and prosperity there is a causal relationship. The reality that occurs, the causal relationship is only enjoyed by certain groups only, and only the matter materialistic. The concept of Islamic economy based on the real sector is considered more relevant to appreciate the causal relationship (economic growth & welfare). The meaning of welfare in Islam is a material & spiritual prosperity called Falah.